2021
DOI: 10.1111/all.15169
|View full text |Cite
|
Sign up to set email alerts
|

Direct oral penicillin challenge for penicillin allergy delabeling as a health services intervention: A multicenter cohort study

Abstract: To the Editor, Some patients with anaphylaxis experience recurrences even when a trigger is identified in the initial reaction. [1][2][3][4][5][6] However, recurrence has received less attention than other epidemiological parameters associated with this condition. [1][2][3][4][5][6] We carried out a systematic review of the international literature to investigate the frequency, severity, and time to onset of recurrence.Details of the methodology of the review are provided in the additional material.After rulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…(Figure 1). Fifty six studies were case series, (Eischens, Wolf et al , Lnumerables and Fischer-Cartlidge , Skibba, Fischer et al , Wrenn, Sarubbi et al 2017, Torney and Tiberg 2018, Blackwell and Khan 2020, Lo, Lacaria et al 2020 , (Harper and Sanchez , Leis, Palmay et al , Adkinson, Thompson et al 1971, Rimawi and Mazer 2014, Jones and Bland 2017, Englert and Weeks 2019, Griffith, Justo et al 2020, Torney and Tiberg 2021 ten were quasi-experimental studies, (Ravindran, Beshir et al 2017 , (Blumenthal, Shenoy et al 2015, Shannon and Krop 2016 two were cohort studies, (Chua, Vogrin et al 2020, Trubiano, Vogrin et al 2022 and one RCT. (Vyles, Chiu et al 2020)…”
Section: Study Inclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…(Figure 1). Fifty six studies were case series, (Eischens, Wolf et al , Lnumerables and Fischer-Cartlidge , Skibba, Fischer et al , Wrenn, Sarubbi et al 2017, Torney and Tiberg 2018, Blackwell and Khan 2020, Lo, Lacaria et al 2020 , (Harper and Sanchez , Leis, Palmay et al , Adkinson, Thompson et al 1971, Rimawi and Mazer 2014, Jones and Bland 2017, Englert and Weeks 2019, Griffith, Justo et al 2020, Torney and Tiberg 2021 ten were quasi-experimental studies, (Ravindran, Beshir et al 2017 , (Blumenthal, Shenoy et al 2015, Shannon and Krop 2016 two were cohort studies, (Chua, Vogrin et al 2020, Trubiano, Vogrin et al 2022 and one RCT. (Vyles, Chiu et al 2020)…”
Section: Study Inclusionmentioning
confidence: 99%
“…The 69 included studies reported on the successful PADL of 5019 patients (adults n= 4314; (Eischens, Wolf et al , Harper and Sanchez , Leis, Palmay et al , Lnumerables and Fischer-Cartlidge , Skibba, Fischer et al , Adkinson, Thompson et al 1971, Rimawi and Mazer 2014, Shannon and Krop 2016, Jones and Bland 2017, Torney and Tiberg 2018, Englert and Weeks 2019, Chua, Vogrin et al 2020, Trubiano, Vogrin et al 2022 heamatology (n=9), (Lnumerables and Fischer-Cartlidge , Trubiano, Thursky et al 2017, Lo, Lacaria et al 2020, Trubiano, Vogrin et al 2022 Emergency Department (n=8), (Eischens, Wolf et al , Rimawi, Cook et al 2013) paediatrics (n=6), (Wong, Timberlake et al 2018 obstetrics & gynaecology (n=5), (Rimawi, Cook et al 2013 peri-operative (n=4), (Harris, Sauberman et al 1999 transplant services (n=3), Fischer-Cartlidge , Trubiano, Thursky et al 2017, Lo, Lacaria et al 2020) infectious diseases (n=4), (Trubiano, Thursky et al 2017, Torney and Tiberg 2018) cardiology (n=2), (Blumenthal, Shenoy et al 2015) urology (n=1), (Blumenthal, Shenoy et al 2015) oral maxillofacial surgery (n=1), (Blumenthal, Shenoy et al 2015) neurology (n=1). (Blumenthal, Li et al 2019) Most studies attempted to de-label those patients with a low allergy risk history only (n=26), (Blumenthal, Shenoy et al 2015, Chua, Vogrin et al 2020, Trubiano, Vogrin et al 2022 moderate risk allergy history only (n=21), , Rimawi and Mazer 2014, Shannon and Krop 2016, Jones and Bland 2017, Torney and Tiberg 2018, Englert and Weeks 2019…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…BL allergy delabelling has been shown to effectively reduce prescriptions of second-line antibiotics and promote re-uptake of first-line penicillins in delabelled patients ( 16 18 ). From Australian experience, antibiotic stewardship was enhanced with increased narrow-spectrum penicillin usage ( 19 ), with a low risk of anaphylaxis recurrence ( 20 ). Economically, delabelling has been shown to generate potential savings of $2000USD per patient-year and switching from other broad-spectrum antibiotics to BL has also been found to lower inpatient and outpatient prescription costs by up to $609USD and $193USD per patient respectively ( 15 , 21 ).…”
Section: Introductionmentioning
confidence: 99%